Trace Elements Measurement In Apricot (Prunus ArmeniacaL.) Seeds By Neutron Activation Analysis - Al-Bachir, M.; Sarhil, A.; Al-Haddad, Th. (Journal of Biotechnology and Biomedical Science, 2018)
Plant food are main sources of elements in human nutrition diet and required for proper growth and body development. Present study involved analyzing the elemental profile attributes of apricot seeds in order to obtain a global pattern of apricot seeds. Trace element in seed of 8 apricot cultivars grown in Syria have been determined using Instrumental Neutron Activation Analysis (INAA). Total of 28 elements namely Potassium (K), Magnesium (Mg), Calcium (Ca), Chlorine (Cl), Sodium (Na), Zinc (Zn), Iron (Fe), Copper (Cu), Aluminum (Al), Manganese (Mn), Rubidium (Rb), Iodine (I), Bromine (Br), Cobalt (Co), Antimony (Sb), Molybdenum (Mo), Chromium (Cr), Mercury (Hg), Barium (Ba), Cadmium (Cd), Cerium (Ce), Lanthanum (La), Selenium (Se), Samarium (Sm), Strontium (Sr), Titanium (Ti), Uranium (U) and Vanadium (V) were determined. The elements present in the apricot seed samples were in the range of levels reported in the literature. The results show that the seed of apricot cultivars grown in Syria is rich in the essential macro and micro-nutrients that are of important in dietary point of view.
Keywords: Trace elements; Apricot seed; Activation analysis; Major elements; Toxic elements